Strategies of Automotive Companies in Argentina: From the Local Model to The Regional Dependent Model (1991-2011) - Naspleda, Federico Daniel (Sociedad y Economía, 2023)
This paper studies the strategies of automotive companies in Argentina during two stages of the country’s transformation: neoliberalism (1991-2001) and post-neoliberalism (2002-2011). It starts from understanding the actions of these companies following the productive and commercial reorganization in MERCOSUR as a response to the development and crisis of the sector during the years 1951-1989, and as part of the country’s accumulation phases. In methodological terms, theories on business strategies are integrated with historical and empirical examinations of production, sales, types of models and trade. The main findingsshow a particular restructuring in automotive production due to changes in corporate tactics. Most of them created a regional market using complementary EBAE strategies that were combined with traditional MS strategies. This allowed them to achieve large-scale manufacturing and to form a technologically dependent M&D model.